Reducing the surface deviation of stereolithography components - Reeves, Philip E. (1998)
The Stereolithography (SL) process has developed into an accurate method of replicating 3D CAD images into tactile objects used for functions such as product evaluation, preproduction testing or as patterns around which tool cavities can be formed. One of the main limitations with the SL process is the surface roughness of parts resulting from the layer manufacturing process. To-date surface roughness has only been reduced using techniques such as additive coating or abrasive finishing. Research has shown however, that these techniques are both detrimental to the accuracy of parts and can prove to increase the cost of SL parts to the end user.